Book Reviews (The Muslim world, 1971)
Book Review in this Articles Studies in Islamic History and Institutions. Bt S.D. Goitein. Dalil al-Mustalahāt al-D?n?ya: Ingl?zi-Arabi (A Wordbook of Relgion: English-Arabic). By Richard W. Thomas. Icon and Minaret: Sources of Byzantine and Islamic Civilization. Edited by Charles M. Foundations of Pakistan: All-India Muslim League Documents, 1906-1947. Edited by Sharifuddin Pirzada Arab Socialism. Edited by Sami A. Hanna and George H. Gardner. Ibn Khaldū in Egypt, His Public Functions and His Historical Research (182-1406): A Study in Islamic Historiography. By Wallter J. Fischel. Middle Eastern Cities, A Symposium on Ancient, Islamic, and Contemporary Middle Eastern Urbanism. Edited by Lra M. Lapidus. The Day of Maysalū: A Page from the Modem History of the Arans. By Abū Khaldū Sä al-Husr?, tr. The Political Awakening in the Middle East. Edited by George Lenczowski. Arab & jew in Israel: A Case Study in a Human Relations Approach in Conflict. By Martin Lakin The Nature of Normadism: A comparative Study of Pastoral Migrations in Southwestern Asia and Northern Africa. By Douglas L. Johnson. Tunisia. By Wilfrid Knapp. The Geography of al-Andalus and Europe, from the book al-Masä wal-Mamolik (“The Routes and the Contries”). BY abū Ubayd al-Bakr?; America and the Mediterranean World, 1776-1882. By James A. Field, Jr. The Amercan Apporach th the Arab World. By John S. Badeau. American University of Be?; Festival Book (Festschrift). Edited by Fuäd Sarrūf and Suha Tamin.